2009
DOI: 10.1099/vir.0.017285-0
|View full text |Cite
|
Sign up to set email alerts
|

Vps4 and the ESCRT-III complex are required for the release of infectious hepatitis C virus particles

Abstract: The mechanisms by which infectious hepatitis C virus (HCV) particles are assembled and released from infected cells remain poorly characterized. In this regard, many other enveloped viruses, notably human immunodeficiency virus type 1, have been shown to utilize the host vacuolar protein sorting machinery (also known as the endosomal sorting complex required for transport; ESCRT) to traffic through the cell and effect the membrane rearrangements required for the formation of enveloped particles. We postulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 47 publications
5
78
0
3
Order By: Relevance
“…Numerous RNA viruses, including retroviruses, rhabdoviruses, filoviruses, flaviviruses, orbiviruses, orthomyxoviruses, and arenaviruses (8,12,16,25,47,52,61) use the ESCRT pathway to release virus particles from the cells. Recent work suggests that a PXXP motif within the HEV ORF3 protein may play a similar role during HEV particle formation (10,45,46,62).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous RNA viruses, including retroviruses, rhabdoviruses, filoviruses, flaviviruses, orbiviruses, orthomyxoviruses, and arenaviruses (8,12,16,25,47,52,61) use the ESCRT pathway to release virus particles from the cells. Recent work suggests that a PXXP motif within the HEV ORF3 protein may play a similar role during HEV particle formation (10,45,46,62).…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, budding occurs concurrently with the release of ESCRT components from the MVB membrane induced by an AAA-ATPase, Vps4, which is present in humans as two isoforms, Vps4A and Vps4B (Babst et al, 1998;Katzmann et al, 2002). Numerous enveloped RNA viruses such as human immunodeficiency virus type 1 (HIV-1) (Garrus et al, 2001), Ebola virus (Martin-Serrano et al, 2001) and avian sarcoma virus (ASV) (Pincetic et al, 2008) and, more recently, hepatitis C virus (HCV) (Ariumi et al, 2011;Corless et al, 2010;Lai et al, 2010) have been shown to utilize ESCRT complexes during virion morphogenesis. Furthermore, enveloped DNA viruses including hepatitis B virus (HBV) (Lambert et al, 2007;Watanabe et al, 2007) and herpes simplex virus 1 (HSV-1) (Crump et al, 2007) have been reported to exploit the MVB machinery.…”
Section: Introductionmentioning
confidence: 99%
“…Both ESCRT-I and Alix can independently recruit ESCRT-III, which together with Vps4 are required for efficient virus budding. Recent studies have shown that ESCRT-III and Vps4 can be recruited independently of either Tsg101 or Alix by the herpes simplex virus type-1 (Pawliczek & Crump et al, 2009) and the hepatitis C virus (Corless et al, 2010). ESCRT-II was found not to be essential for HIV-budding (Langelier et al, 2006), however ESCRT-II was discovered recently to be essential for release of the avian sarcoma virus (Pincetic et al, 2008).…”
Section: Viral Infectionsmentioning
confidence: 99%